LAPORAN TUGAS AKHIR PROSES PERAN SUTRADARA DALAM PROSES PRODUKSI FILM DOKUMENTER "DIBAWAH ATAP: ANTARA KELUARGA DAN POLITIK" - Jennifer Evelyn Samosir (2023)
This work was created with the aim of providing an outlook on the role and position of women in politics. With the facts and the reality that in Indonesia the political world is still dominated by the participation of men, women needs extra struggle compared to men themselves. This arises from the social view that even in general women are still considered not ideal to work or to have a profession, especially women who are housewives. The final result of this documentary film also shows the role of the director, where a director has a strong role in making a documentary film from the pre-production to post-production stages. The most important thing in the role of a director is to have a strong vision of the film, and be able to communicate, combine all parties involved in order to create a smooth and good work process. The director also plays a full role in making decisions, especially during the shooting process.